Hydrogen sulfide emission sources, regulations, and removal techniques: a review - Habeeb, Omar Abed; K., Ramesh; Ali, Gomaa A. M.; Sethupathi, Sumathi; R. M., Yunus (Walter de Gruyter, 2018)
This review highlights the recent technologies of H2S removal from wastewater in the petroleum refinery. H2S is a harmful, putrid, and hazardous gaseous compound. The main processes such as physicochemical, chemical, biological, and electrochemical methods were compared and discussed in detail. The effects of various parameters and adsorbent characteristics were highlighted and correlated with the adsorption capacities. Surface functional groups and porosity surface area play a crucial role in the process of single-phase and composite adsorbents. Composite materials impregnated with some metals showed high removal efficiencies. It was found that the adsorption process is the most relevant way for H2S removal due to its high removal efficiency, low cost, eco-friendly, and operational simplicity. This study serves as a useful guideline for those who are interested in H2S removal.